Managing employee relations in the hotel and catering industry - Lucas, Rosemary E. (London : Cassell, 1995)
This book is divided into three parts: The employee relations, managerial and employment contexts; The employment relationship; and Legal and social issues.
Keywords: Hospitality industry; Hospitality industry -- Personnel management